2021
DOI: 10.1038/s41598-021-85847-6
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic nutrient loads and season variability drive high atmospheric N2O fluxes in a fragmented mangrove system

Abstract: Fragmented mangroves are generally ignored in N2O flux studies. Here we report observations over the course of a year from the Mangalavanam coastal wetland in Southern India. The wetland is a fragmented mangrove stand close to a large urban centre with high anthropogenic nitrogen inputs. The study found the wetland was a net source of N2O to the atmosphere with fluxes ranging between 17.5 to 117.9 µmol m−2 day−1 which equated to high N2O saturations of between 697 and 1794%. The average dissolved inorganic nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Under favourable conditions, high N load accelerates the production of the most potent greenhouse gas N 2 O (Hershey et al, 2019;Nobrega et al, 2013Nobrega et al, , 2016Suarez-Abelenda et al, 2014) with potential effects on ecosystem services, contributing to atmospheric N 2 O budget. Hershey et al (2021) reported that in the MCW, dissolved organic (DON)…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Under favourable conditions, high N load accelerates the production of the most potent greenhouse gas N 2 O (Hershey et al, 2019;Nobrega et al, 2013Nobrega et al, , 2016Suarez-Abelenda et al, 2014) with potential effects on ecosystem services, contributing to atmospheric N 2 O budget. Hershey et al (2021) reported that in the MCW, dissolved organic (DON)…”
Section: Discussionmentioning
confidence: 99%
“…Hershey et al. (2021) reported that in the MCW, dissolved organic (DON) and inorganic nitrogen (DIN) concentration was in range with other higher polluted estuaries and acted as a source of atmospheric N 2 O (Hershey et al. 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations